The Problem of Journal Supplements in a Sharing World. Issue 4 (2nd October 2022) - vanDuinkerken, Wyoma; Valdes, Zachary
Abstract: This quantitative longitudinal study cross-analyzes a shared print repository's periodical supplement records against physical copies to determine the accuracy of bibliographic representation for bound supplements. The authors relate the study's findings to collection managers and library administrators by highlighting prominent issues discovered, and by discussing the challenges this descriptive disconnect may present for shared repositories, as well as any library collection containing periodical supplements. By requesting that participating libraries provide catalog records for materials set to be submitted, the shared print repository central to this study was well positioned to access and analyze large samples of records and materials from an assortment of independent library collections. It was discovered that many periodical supplement records failed to fully represent actual supplement content held, particularly when involving supplements that were bound together with serial volumes. As a result, the authors pose that if relying only on standard supplement cataloging requirements to represent periodical supplement holdings, it may be particularly difficult for those overseeing collection management to know exactly what supplement content is held and bound within or apart from the affiliated parent resource materials. In turn, this issue may result in libraries inadvertently mislaying or discarding valuable supplement content, particularly when supplement information is not recorded and cataloged at the item level.